(2S,NS)-N-Allyl-N-benzyl-1-hydroxy-3-(4-hydroxyphenyl)-N-methylpropan-2-aminium bromide - Hua-Fang Wu; Ying-Gang Luo; Kai-Bei Yu; Guo-Lin Zhang; Xin-Fu Pan (Acta Crystallographica Section E, 2008)
The title compound, C20H26NO2+·Br−, is an N-chiral quaternary ammonium salt synthesized from (2S*)-N-benzyl-N-methyltyrosine methyl ester. The dihedral angle between the phenyl ring and the benzene ring is 11.61 (19)°. In the crystal structure, the allyl group is disordered over two positions with site occupancy factors of ca 0.8 and 0.2. The bromide anion links to the quaternary ammonium cations via O—H...Br hydrogen bonding. An intramolecular O—H...Br hydrogen bond is also observed.